Protocol: A randomized controlled trial to assess effectiveness of a 12-month lifestyle intervention to reduce cardiovascular disease risk in families ten years after pre-eclampsia (FINNCARE) - Tiina Jääskeläinen; Anni Kivelä; Michelle Renlund; Seppo Heinonen; Minna Aittasalo; Hannele Laivuori; Taisto Sarkola (Preventive Medicine Reports, 2022)
Pre-eclampsia (PE) is a multisystem progressive disorder affecting 3–5% of pregnancies. PE independently increases the risk for premature cardiovascular disease (CVD) in mothers and their children long-term. The effectiveness of a family-centered lifestyle intervention to lower CVD risk in PE families has not previously been evaluated. In the current FINNCARE study, we prospectively compare CVD risk and CVD progression in PE families (mother, father and child) in a cross-sectional study setting 8–12 years from delivery with non-PE control families of comparable age. Furthermore, we evaluate the effectiveness and feasibility of an interactive web-based behavioral 12-month lifestyle intervention to reduce blood pressure and the CVD risk profile overall in a randomized controlled trial. In total, 300 PE families will be randomized 1:1 to a PE-intervention or a PE-control group, and the 100 non-PE control families similarly followed-up at 12 months. Primary outcome is 24-hour mean systolic BP change from baseline in mother and child. Study aims to provide information on CVD progression and CVD risk management in the family following PE.